Primary school teachers [sic] perceptions of gender-based differences : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Booth, Ingrid (Massey University, 2014)
This study explores primary school teachers [i.e. teachers'] perceptions of gender-based differences in primary school in New Zealand. In this mixed-method study, the research utilised an online survey to collect data in three domains: teacher as self, teacher-student dynamics, and teacher collegiality. Quantitative analysis revealed overall no differences; however, quantitative analysis showed differences in the participants' perceptions of teachers content knowledge, the ability to treat students fairly, and teachers' positive attitude toward the profession. Qualitative analysis also revealed differences in participants' perceptions of the jobs held by males and females in the primary sector with male teachers receiving more negative responses when compared to female primary teachers. Furthermore all of the participants perceived a need for more male primary teachers in the primary sector. The participants were unsure if male teachers had an adequate amount of content knowledge and whether female teachers treated their students fairly. The participants perceived that males [i.e. male] teachers' attitudes toward the profession was not as positive as female teachers' attitudes toward the profession. Male primary teachers' [i.e. teachers] are always in demand in primary schools in New Zealand; but could that be for the wrong reasons? The literature has cast doubt on the common assumptions that male teachers are needed as male role models and that their presence can improve the behaviour and academic achievement of boys. The literature suggests that men in the primary teacher workforce are often viewed in terms of their inherent male qualities rather than personal attributes; their ability to be a role model rather than their caring qualities and ability to build relationships. The research findings provide insight into primary teachers perceptions of gender-based differences and could lead to improved teacher education and professional development programs as well as the recruitment of more effective male primary teachers.
Primary school teachers' perceptions of gender-based differences : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand
Keywords: Primary school teachers; Gender differences in education; Male primary school teachers